OPTIMIZATION OF COATING MATERIAL FOR SUSTAINED RELEASE VENLAFAXINE HYDROCHLORIDE TABLET: Pharmaceutical Science-Pharmaceutics - ANSHUL JAIN; RAJENDRA CHAUHAN; SATYAVEER SINGH; SUNISHA KULKARNI; SUMAN JAIN (International Journal of Life Science and Pharma Research, 2022)
Venlafaxine is widely prescribed for the treatment of depression, depression with associated symptoms of anxiety, generalized anxiety disorder and social anxiety disorder. Because of its short half life, multiple dosing is required to maintain blood concentration. A properly designed, sustained release dosage form of venlafaxine will show uniform pharmacological response and reduce the frequency of administration. The present research endeavor was directed towards the optimization and development of proper coating dispersion to produce a sustained release dosage form of venlafaxine. Hydrophobic and hydrophilic polymers were tried in combination to obtain a desired release profile. The aqueous coating surpasses the environmental and hazardous problem of organic coating while in other perspective organic coating reduces the process time of aqueous coating. Reservoir type aqueous and organic coated once daily sustained release tablets of venlafaxine were successfully formulated using Eudragit® RS30D, Eudragit® RL30D, Aquacoat ECD 30(ethyl cellulose), Eudragit® RSPO and Eudragit® RLPO as coating materials.